Efficient design in building construction with rubber bearing in medium risk seismicity: case study and assessment - Islam, A. B. M. Saiful; Ahmad, Syed Ishtiaq; Jumaat, Mohd Zamin; Hussain, Raja Rizwan; Rahman, Muhammad Ashiqur; Darain, Kh Mahfuz ud (Journal of Civil Engineering and Management, 2014)
Earthquakes pose tremendous threats to life, property and a country's economy, not least due to their capability of destroying buildings and causing enormous structural damage. The hazard from ground excitations should be properly assessed to mitigate their action on building structures. This study is concerned with medium risk seismic regions. Specifically, the heavily populated capital city Dhaka in Bangladesh has been considered. Recent earthquakes that occurred inside and very close to the city have manifested the city's earthquake sources and vulnerability. Micro-seismicity data supports the existence of at least four earthquake source points in and around Dhaka. The effects of the earthquakes on buildings are studied for this region. Rubber base isolation is selected as an innovative option to lessen seismic loads on buildings. Case studies have been carried out for fixed and isolated based multi-storey buildings. Lead rubber bearing and high damping rubber bearing have been designed and incorporated in building bases. Structural response behaviours have been evaluated through static and dynamic analyses. For the probable severe earthquake, rubber bearing isolation can be a suitable alternative as it mitigates seismic effects, reduces structural responses and provides structural and economic benefits.